ANALISIS BATAS UMUR PERKAWINAN DI INDONESIA DALAM PERSPEKTIF UNDANG-UNDANG NO. 16 TAHUN 2019 DAN Q.S AL-ṬALAQ AYAT 4: PENDEKATAN MAQASID SYARIAH - Mufrod, Mufrod Teguh Mulyo; Nehru, Nehru Millat Ahmad; Munifah, Munifah (Kopertais Wilayah X Jawa Tengah, 2025)
This study examines the legal marriage age based on Law No. 16 of 2019 and Q.S Al-Ṭalaq [65]: 4 using Jasser Auda’s Maqasid Syariah approach. It analyzes the differences between positive law, which sets the minimum marriage age at 19, and Islamic law, which does not specify an explicit age but emphasizes physical, mental, and emotional maturity. Employing a qualitative method with content analysis, this study explores the marriage age framework in light of Maqasid Syariah, focusing on preserving individual and familial welfare. The findings reveal that Islamic law allows flexibility in marriage age, provided specific criteria, including readiness in knowledge, mental, psychological, reproductive, and material aspects, are fulfilled. Jasser Auda’s holistic approach highlights the importance of considering social, cultural, and long-term impacts, such as preventing stunting, domestic violence, and family dysfunction. This study concludes that while the marriage age set by positive law is binding, the principles of Maqasid Syariah can bridge the gap between perspectives, fostering the establishment of harmonious families aligned with Islamic values. Consequently, this research offers significant contributions to integrating positive legal norms and Islamic principles to ensure comprehensive family and societal protection.